The Use of Ethnomedicine in South Brebes As The Basis For The Development of Traditional Medicine Independence - Resa Frafela Rosmi; Sri Wartulas; Siti Nur Halimah; Aulia Turrohmah (Riviera Publishing, 2025)
Indonesia is a country with very high biodiversity, including in terms of medicinal plants. In various regions, including South Brebes, traditional medicine practices based on local knowledge or ethnomedicine are still used by the community to overcome various health problems. This research aims to explore and document the ethnomedicine practices of the South Brebes community as the first step toward the independence of traditional medicine raw materials based on local wisdom. This study uses qualitative research methods. Data processing is described descriptively and presented in the form of tables and graphs. The results show that people in the South Brebes area, especially in Bumiayu, Tonjong, Paguyangan, and Benda Districts, are still actively using plants as traditional medicine to overcome various health problems, both mild and chronic. It is recorded that there are 73 species of plants used, with the leaf being the most dominantly used, followed by fruits, rhizomes, seeds, tubers, and other parts. The use of these medicinal plants includes the treatment of various diseases such as colds, fever, indigestion, hypertension, gout, diabetes, urinary tract infections, and chronic diseases such as stroke, cancer, and heart disease. In addition, medicinal plants are also used for body care purposes, such as facilitating menstruation, strengthening vitality, maintaining healthy skin, and increasing immunity. The existence and utilization of these medicinal plants reflect the local wisdom of the community in maintaining natural health and show great potential to be further developed in efforts to preserve and develop traditional medicines based on local biodiversity.